Ekspresi Seni Masyarakat Tradisional Desa Adat Penglipuran Bangli Sebagai Sarana Pemujaan Kepada Tuhan (Kajan Bentuk, Fungsi, Dan Makna) - I Nengah Duija (Institut Seni Indonesia Denpasar, 2008)
In Balinese Culture art is substantial because it closely relates to the system of belief especially Hindu religion. Thus art is having inner power that is the spirit of the purity of Hindu itself. Therefore functionally art in Bali can be categorized into: seni wali, bebali and balih-balihan. The intensity of art activities relate to the ritualistic performance of Balinese Hindu society. In Ba- linese traditional society art activities relate to religious ritual are frequently performed even melted into the life of their rites. Likewise in the village of Adat Penglipuran Bangli, has expressed that art as an act of worship in the form of sacred Baris Dance. The performance of sacred Baris dance in the village of Adat Pengli- puran has form, function and meaning pertaining to worship, both to ancestors (cosmic axis) at Bayung Gede Kintamani and to God. The aesthetic concept that is used as a mean of worship borne theo- aesthetic term. Because of having those functions and meaning this sacred tradition survive. Besides that, this sacred Baris Dance as honor to geographical reality that has its upper reach at mountain, so it’s value-oriented is on war myth, fertility, water, etc. Thus the artistic expression of Penglipuran society as worship rites toward the Creator.